The Main Directions Of Education Of The Younger Generation With An Active Civic Position - Ulmasbek Karimov (Periodica Journal, 2025)
The complex measures taken to create all the favorable conditions for the comprehensive development of the growing young generation in the country have become a feature of our people and become an integral part of our national nature. It has long been an important issue in every family, in every neighborhood, first of all, to ensure the health of young people, to give them good knowledge, and at the same time to reach adulthood as worthy individuals with high spiritual and moral qualities. During the years of Independence, these tasks were raised to the level of Public Policy in Uzbekistan, which began to make it possible to achieve high achievements in all areas.
Keywords: civil society; civil position; upbringing